Numerical solution of two-dimensional fuzzy Fredholm integral equations of the second kind using triangular functions - Farshid Mirzaee; Mohammad Komak Yari; Elham Hadadiyan (Beni-Suef University Journal of Basic and Applied Sciences, 2015)
The main purpose of this paper is to approximate the solution of linear two-dimensional fuzzy Fredholm integral equations of the second kind (2D-FFIE-2). We use fuzzy two-dimensional triangular functions (2D-TFs) to reduce the 2D–FFIE–2 to a system of linear Fredholm integral equations of the second kind with three variables in crisp. More over, we prove the convergence of the method. Finally we illustrate this method with some numerical examples to demonstrate the validity and applicability of the technique.